2008
DOI: 10.1136/ard.2008.091405
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of B cell activating factor (BAFF) in subsets of patients with idiopathic inflammatory myopathies

Abstract: Our finding of elevated serum levels of BAFF in patients with myositis with described phenotypes together with the correlations between levels of BAFF and CK and a negative correlation with dose of glucocorticoids, indicate that BAFF could be a potential therapeutic target in such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 39 publications
(37 reference statements)
4
66
1
1
Order By: Relevance
“…21,22 Nodular collections of inflammatory cells in muscle containing dense B-cell-rich centers were reported in 1996 in patients with connective tissue disorders with muscle involvement (''overlap syndromes''), but no such nodules were seen in patients with IBM, PM, or DM. 23 In our studies, we found nodular collections in 50% of patients with IBM, PM, and DM.…”
Section: Discussionmentioning
confidence: 98%
“…21,22 Nodular collections of inflammatory cells in muscle containing dense B-cell-rich centers were reported in 1996 in patients with connective tissue disorders with muscle involvement (''overlap syndromes''), but no such nodules were seen in patients with IBM, PM, or DM. 23 In our studies, we found nodular collections in 50% of patients with IBM, PM, and DM.…”
Section: Discussionmentioning
confidence: 98%
“…Some patients relapsed as their B-cell pools repopulated and depletion of autoantibody titres was variable (Chung, Genovese, & Fiorentino, 2007;Cooper et al, 2007;Levine, 2005). The potential of B-cells as therapeutic targets is further supported by the elevations in serum levels and gene expression of B-cell activating factor (BAFF) in IM patients, a cytokine crucial for B-cell maturation and survival, which is also thought to play a role in autoantibody production (Krystufkova et al, 2008;Salajegheh et al, 2010). Despite all the evidence described here implicating B-cells and loss of B-cell tolerance in the IM, numerous questions still remain to be resolved, including identification of the stimulating antigens and epitopes, sequence characteristics and pathogenicity of highaffinity, antigen-specific antibodies produced in situ, and the factors regulating and controlling these autoimmune reactions.…”
Section: Discussionmentioning
confidence: 89%
“…Serum IL-4 is increased in both patients with dermatomyositis 40 and those with Sjögren syndrome, 41 and IL-4 knockout mice lack immune-mediated secretory dysfunction. 42 Moreover, there was increased BAFF in both patients with dermatomyositis 43 and those with Sjögren syndrome. 44 In patients with Sjögren syndrome, BAFF levels correlated with Sjögren syndrome Disease Damage Index.…”
Section: Discussionmentioning
confidence: 99%